Collapsing Focal Segmental Glomerulosclerosis in Viral Infections - Muehlig, Anne K.; Gies, Sydney; Huber, Tobias B.; Braun, Fabian (Frontiers in Immunology, 2022)
Collapsing glomerulopathy represents a special variant of the proteinuric kidney disease focal segmental glomerulosclerosis (FSGS). Histologically, the collapsing form of FSGS (cFSGS) is characterized by segmental or global condensation and obliteration of glomerular capillaries, the appearance of hyperplastic and hypertrophic podocytes and severe tubulointerstitial damage. Clinically, cFSGS patients present with acute kidney injury, nephrotic-range proteinuria and are at a high risk of rapid progression to irreversible kidney failure. cFSGS can be attributed to numerous etiologies including viral infections like HIV, cytomegalovirus, Epstein-Barr-Virus and parvovirus B19 as well as drugs and severe ischemia. Risk variants of the APOL1 gene, predominantly found in people of African descent, increase the risk of developing cFSGS. Patients infected with the new Corona-Virus SARS-CoV-2 display an increased rate of acute kidney injury (AKI) in severe cases of COVID-19. Besides hemodynamic instability, cytokine mediated injury and direct viral entry and infection of renal epithelial cells contributing to AKI, there are emerging reports of cFSGS associated with SARS-CoV-2 infection in patients of mainly African ethnicity. The pathogenesis of cFSGS is proposed to be linked with direct viral infection of podocytes, as described for HIV-associated glomerulopathy. Nevertheless, there is growing evidence that the systemic inflammatory cascade, activated in acute viral infections like COVID-19, is a major contributor to the impairment of basic cellular functions in podocytes. This mini review will summarize the current knowledge on cFSGS associated with viral infections with a special focus on the influence of systemic immune responses and potential mechanisms propagating the development of cFSGS.